Ícones Urbanos: tecnologia e propaganda na transformação da identidade e orgulho urbanos - Correia, Beatriz Silva (2006)
The current investigation uses the qualitative search method, essentially bibliographic and field experiences. Deals with the forms to interfere with the cities, since that the Humankind developed technological processes and established in organized societies. Our mainly interest is on the symbolic object, in the space concept, and what it can be understood as chosen place. The technique for urban planning, the punctual interventions, the real estate enterprises, all these takes part of the urban construction and the variety of instruments creating new meanings for its population. The association between technology and the city provokes people to formulate utopias, which multiply themselves with the industry, speculation and fantasy. The object-symbol alludes to reflection of paradise and the search of a place with meaning. The sensation of identity and urban pride grows in this environment, interconnecting the real city and the imagined city. The concept of social identity is present to spread the sense of integration, leading planners to find out inspiration in the ancestral icons and nature, creating historical interconnections. Museum Oscar Niemeyer, Guggenheim Museum, Historical Centers of Santa Clara and São Paulo, Puerto Madero and Avenida Revolución are interventions that breaks the monotony, appeal the curiosity, generate discussions and promote transformations in the dynamic of the place. The technology in architectural objects is transformed into icons unlocking human movements that will redefine the concept of urban identity and pride.